Association between Argyrophilic Proteins of Nucleolar Organizer Regions, Clinicomorphological Parameters, and Survival in Non-Small-Cell Lung Cancer. (2nd January 2014) - Kobyakov, Dmitriy; Klimachev, Vladimir; Avdalyan, Ashot; Bobrov, Igor; Bychkova, Elena; Kruglova, Natalia; Lazarev, Aleksandr; Lushnikova, Elena; Nepomnyashchikh, Lev
Abstract : We studied argyrophilic proteins associated with nucleolar organizer regions (AgNOR) in non-small-cell cancer. We determined the area index (AI) and coefficient of variation (CV) of AgNOR. AI is associated with the key clinicomorphological parameters within the TNM system:T andN values, greatest tumor dimension up to 3 cm and more, disease stage, histogenesis, and tumor differentiation. CV is associated withT value, greatest tumor dimension up to 3 cm and more, histogenesis, and tumor differentiation. Survival of patients is longer in low AI or CV values versus high AI or CV values, longer in low AI and CV values (−AI/−CV type), shorter in high AI and CV values (+AI/+CV type), and intermediate in opposite AI and CV values (−AI/+CV and +AI/−CV types). Independent predictors in non-small-cell lung cancer includeN value, greatest tumor dimension, histogenesis, and CV. Assessment of quantitative values and heterogeneity of AgNOR is important for differential diagnosis and prognosis of non-small-cell lung cancer.